Fracturing simulation with different perforation positions at deep coal seam and roof/ floor rock — case study at the No.8 deep coal seam of a gas field in the Ordos basin - Dong XIONG; Jiayuan HE; Xinfang MA; Zhaoliang QU; Tiankui GUO; Shiyu MA (Meitan xuebao)
The No.8 deep coal seam in the Ordos basin is situated at a burial depth of over 2 000 meters and has a complex geological structure. The roof and floor layers of the target coal seam are composed of limestone and mudstone, respectively. Horizontal well fracturing is used on-site as a development method for the No.8 deep coalbed methane. A finite element simulation implementation process has been developed to help clarify the propagation path law of hydraulic fractures in the No.8 deep coal seam. This process takes into account the reservoir geological structure, wellbore trajectory, and mechanical characteristics of reservoir rock to simulate hydraulic fracturing with different perforation positions at the coal seam and roof/ floor rock. Firstly, the rock specimens from the reservoir are processed, and their mechanical properties are tested using triaxial compression experiments. The characteristics of the matrix pores and fracture structures are analyzed by using CT scanning. Then, the cohesive model with pore pressure nodes is used to understand the impact of weak surfaces and pore fractures on the fluid seepage within deep coal seam. A three-dimensional finite element model of deep coal seam hydraulic fracturing is established which considers the seepage - stress - damage coupling. The parameters of the model are inverted and verified based on on-site fracturing testing and construction technology. Finally, the simulation of fracturing are conducted with different perforation positions at deep coal and roof/ floor rock. According to the research findings, the following results are obtained: The coal rock has a lower elastic modulus and a higher Poisson’s ratio than the limestone and mudstone rocks, and the pores and fractures are developed. When perforating in the coal seam, the hydraulic fractures are completely limited to the expansion of the coal seam. It is difficult for hydraulic fractures to pass through the interface to enter the limestone and mudstone. The hydraulic fractures are wholly closed before reaching the peak injection rate. When perforating in the limestone, the hydraulic fractures propagate into the coal seam by passing through the interface between the coal and limestone, and they expand further into the coal seam. It is worth noting that the length of hydraulic fractures in the coal is greater than that in the limestone. When perforating in the mudstone, the hydraulic fractures propagate into the coal seam by passing through the interface between the coal and mudstone. The hydraulic fractures in both mudstone and coal are extended in length. The perforation in limestone and mudstone requires a higher initiation pressure compared to the perforation in coal. During the perforation in the limestone and the mudstone, the hydraulic fractures in the coal tend to close first, due to the filtration of a significant amount of fracturing fluid in the coal. The research results provide some ideas for modeling the expansion of hydraulic fractures in deep coal seams and guide the efficient development of deep coalbed methane.